2003
DOI: 10.1056/nejmoa035026
|View full text |Cite|
|
Sign up to set email alerts
|

Enfuvirtide, an HIV-1 Fusion Inhibitor, for Drug-Resistant HIV Infection in North and South America

Abstract: The addition of enfuvirtide to an optimized antiretroviral regimen provided significant antiretroviral and immunologic benefit through 24 weeks in patients who had previously received multiple antiretroviral drugs and had multidrug-resistant HIV-1 infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

13
559
1
12

Year Published

2004
2004
2015
2015

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 845 publications
(585 citation statements)
references
References 15 publications
13
559
1
12
Order By: Relevance
“…Currently, treatment for such diseases focuses on drugs and vaccines that specifically target the viral proteins or inhibit host-viral interactions 2,3 . However, the nature of lentiviral infections, whereby the virus, such as human immunodeficiency virus (HIV), invades immune cells and integrates into the host genome to establish its latent infection, has created a huge obstacle with respect to developing efficient vaccines 4,5 .…”
mentioning
confidence: 99%
“…Currently, treatment for such diseases focuses on drugs and vaccines that specifically target the viral proteins or inhibit host-viral interactions 2,3 . However, the nature of lentiviral infections, whereby the virus, such as human immunodeficiency virus (HIV), invades immune cells and integrates into the host genome to establish its latent infection, has created a huge obstacle with respect to developing efficient vaccines 4,5 .…”
mentioning
confidence: 99%
“…Because of the persisting difficulties in developing a vaccine against HIV (1), the discovery of drugs to treat infected people and of prophylactic agents to prevent HIV infection remains a critical medical need. Despite considerable progress on this front, an increasing number of patients ultimately become resistant to highly-active antiretroviral therapy (HAART) because of the emergence of variants that are resistant to current treatment regimens (2). Moreover, patients may become infected with virus already resistant to multiple drugs (3), highlighting the need for continuous development of novel agents.…”
mentioning
confidence: 99%
“…Although several HIV-1 entry inhibitors have been evaluated in clinical trials and have shown promising prospects for therapy (1,28), the only entry inhibitor licensed to date is the fusion inhibitor enfuvirtide (ENF; also called T20), which has shown potent antiviral activity in patients, resulting in sustained viral load reduction when used in combination with an optimized background regimen of protease and/or reverse transcriptase inhibitors (21)(22)(23). Similar to results with other antiviral agents, however, ENF-resistant HIV-1 variants may emerge under the selective pressure of ENF (26,32,39,42) whenever the treatment fails to completely suppress viral replication in vivo.…”
mentioning
confidence: 99%